Historical view of Medical Education - Salaverry García, Oswaldo (1998)
The historical relationship, with a back-view to the Greek origin going through the formation period of medical schools within mediaeval universities, is described. We briefly develop the mediaeval pattern of Medical Education sat in the Americas after the Spanish Conquer and its permanence until the formation of the San Fernando Medical School by Hipolito Unanue.